A hazard identification digital simulation game developed based on the extended authentic learning framework. Issue 3 (10th March 2022) - Safiena, Sufiana; Goh, Yang Miang
Abstract: Background: Previous research has shown that the inability to identify hazards is the leading cause of workplace accidents and fatalities. The lack of competency in hazard identification implies a crucial need to improve the teaching and learning approaches in construction safety training and education. Purpose/Hypothesis: This study developed the extended authentic learning framework (EALF) to design a digital simulation game (DSG) called SafeSim Hazards and tested students' perception of its effectiveness in workplace safety and health (WSH) education. Design/Methods: Undergraduates majoring in Project and Facilities Management (PFM) used SafeSim Hazards to learn about hazard identification. A questionnaire was used to collect student perceptions of the game and its effectiveness. In addition, random forest analyses were used to identify critical factors that affect the perceived achievement of learning outcomes. Results: Guidance is the most influential authentic learning factor, and game interaction is an essential design factor in influencing the perceived achievement of learning outcomes. Notably, participants reported high acceptance toward SafeSim Hazards with an average rating of 3.36 out of 4. Conclusions: The key contributions of this study are threefold: (1) An EALF is developed to facilitate the development of construction hazard identification DSG. (2) It is demonstrated that the DSG developed based on EALF is well received by students with minimum construction experience. (3) It is recommended that future construction hazard identification DSG for inexperienced trainees should emphasize guidance and game interactions.